Pulsed Acoustic Cellular Expression (PACE) reduces capsule formation around silicone implants - Reichenberger, Matthias; Heimer, Sina Franziska; Lass, Ulrike; Germann, Günter; Köllensperger, Eva; Mueller, Wolf; Hirsch, Tobias; Fischer, Sebastian (Aesthetic plastic surgery, 2014)
Capsular contracture remains a major complication after reconstructive or aesthetic breast augmentation. Formation of capsular fibrosis is a multifactorial process. An initial inflammatory reaction appears to be key to the development of capsular contracture. Recent studies have shown that pulsed acoustic cellular expression (PACE) has significant antiinflammatory effects. Thus, this study aimed to determine the potential of PACE to prevent or attenuate capsular contracture around silicone implants in a rodent model. For this study, 36 Lewis rats were divided into two groups, and a textured silicone implant was placed in a dorsal submuscular pocket. One group received PACE treatment, whereas the other group served as the control group and received no treatment. Follow-up evaluations were performed after 10, 35, and 100 days. Capsule thickness, collagen density, myofibroblasts, vascular density, and a semiquantitative real-time polymerase chain reaction that addressed differential gene expression were assessed. The PACE treatment significantly reduced capsule thickness on days 10, 35, and 100 compared with the control group (day 10: 632.9 ± 164.5 vs 932.6 ± 160.8, p < 0.05; day 35: 709.5 ± 175 vs 825.9 ± 313.3, p < 0.0.5; day 100: 736.3 ± 198.1 vs 1,062.3 ± 151.9, p < 0.05). This was accompanied by a significant suppression of proinflammatory genes (cluster of differentiation 68, monocyte chemotactic protein-1, CCL4) and synergistic alterations of pro- and antifibrotic proteins (transforming growth factor-beta 1, matrix metalloproteinase-2). This study showed that the PACE application significantly reduces capsular contracture around silicone implants. A decrease in capsular thickness after PACE treatment seems to be associated with a downregulation of proinflammatory genes and proteins. The study identifies PACE technology as a potential low-cost technique that is easy to use for reduction of capsular contracture after augmentation using silicone implants.